The development of fair labour practice guidelines at line management level in a construction company - Owen, K. H.(Kevin Hugh) (Stellenbosch : Stellenbosch University, 2012)
Study project presented in partial completion of degree (M. B. A.) -- University of Stellenbosch, 1989.